(untitled) (ENTHYMEMA, 2023)
In the context of the rise of the novel in eighteenth-century Britain, this article examines the understudied production of Elizabeth Helme (c. 1743-1814), who enjoyed a long and successful career as a writer of novels, as a translator and essayist. Special attention will be paid to Helme’s reception in the English press and the translations of her novels into Spanish and French. It will further argue that Helme’s own practice as author, translator, and translated author configured a synergy of knowledge-building that allowed her to articulate her own style as a writer and posed a critical reflection about the art of writing, particularly in her non-fiction work that remains largely unexplored. More generally, Helme’s eclectic approach is indicative of the ways in which eighteenth-century translation and writing practice can foster reflection on literary theory and criticism by confronting the author with the function of their own work.